Optimization of Emprit Ginger Oil Yield through Operating Temperature with Microwave Ultrasonic Steam Diffusion Method - Gilang Maulana Alif; Irfiani Nurul Mawaddah; Fikaputri Rohmatul; Zel Andesra (Institut Teknologi Adhi Tama Surabaya, 2021)
Essential oil of ginger (zingiberene oil (C15H24)) is one of the diversified products that have high selling value. Most of the essential ginger products available in the market haven’t allow the standard export products, based on the Essential Oil Association of USA (EOA) standards. The low quality of ginger essential oil products is due to its production process with conventional distillation. This method is most often used because it is easy to operate and produce a good enough product but takes a long time. Another extract method developed is Microwave Distillation and Simultaneous Solid-Phase Microexctraction (MDSS- PM). In this method the time required is faster but the resulting product is not as good as Hydrodistillation product and requires high energy. In this research, ginger extraction process using Microwave Distillation method is modified by ultrasonic addition technique (MUSDf). The variables used in this research are Steam Diffusion (SDF) method, Microwave Exctraction (ME), Microwave Steam Diffusion (MSDf), Microwave Ultrasonic Steam Diffusion (MUSDf) with 30, 50,70, 90 and 110 minutes extension time and extraction temperature variations of 90, 95, 100 and 1050C. From the result of the research, it is found that the best method to produce ginger oil extract is by using MUSDf method with yield of 0.952%, zingiberene level is 6.38%, and the cost per gram of oil is Rp 17,964.